From Introspection to Action: Connecting Spirituality and Civic Engagement - Kirsch, Gesa E (College composition and communication, 2009)
In recent years, composition scholars have touched on the nature of spirituality in a number of contexts: the rhetoric of preaching (e.g., Moss; Mountford), of silence (e.g., Belanoff; Elbow, "Silence"; Gere; Glenn), of listening (e.g., Ratcliffe), of recovery (e.g., Daniell), of sustainability and the natural world (e.g., Herndl and Brown; Killingsworth and Palmer; Owens; Weisser and Dobrin); and two edited volumes explicitly explore spiritual aspects of rhetoric and writing studies (Bizzell; Foehr and Schiller). Like Bishop, I worry that exploring spirituality in the classroom can easily turn into an anti-intellectual enterprise that defies analysis, critique, and debate-the exact opposite of what higher education sets out to do.5 Contemplative Practice and Spiritual Autobiography Given my reservations, it was more by chance than by design that I decided to add spiritual autobiography as one assignment to a creative nonfiction course.6 What I discovered is that reflection and introspection, two aspects that the assignment introduced, can become a powerful force, leading students to serious and sustained writing, thoughtful inquiry, and deep engagement with a variety of topics.\n I came to realize that it was important for this student to examine her changing values, and that many other courses in her college curriculum (e.g., psychology, sociology, ethics, literature, philosophy) could have just as easily sent her on the same quest to explore-and question-her life's goals and values.